The Design of Tube Houses in Vietnam According to The Orientation of Wellness Architecture - Nguyen, Van Tin; Nguyen, Hong Loan (International Journal of Sustainable Construction Engineering and Technology, 2024)
In modern architecture, the focus on wellness is a growing trend. The goal of the Wellness architecture is to create spaces that enhance the health, wellness, and comfort of building occupants, while also improving the overall sustainability of the building. The WELL Building Standard (WELL) is applied to many housing projects to improve the quality of the living environment. Tube houses are typical and popular housing architecture in most Vietnamese cities with the need to improve the quality of living space. The objective of the article is to propose the design orientation of tube houses in Vietnamese cities according to the trend of Wellness architecture. The research methods include: collecting documents, analysis-synthesis, and systemization. Research results provide solutions according to the main factors of tube house architecture such as landscape environment, architectural characteristics, and interior and micro-climate conditions. The conclusions will contribute to practical design work and may complement and refine the standards and stakeholder opinions on the development and management of tube houses in Vietnam in the future.